A STUDY ON CONSUMER BEHAVIOR AND THEIR DECISION ON CHOOSING AN ARTIFICIAL TURF FOOTBALL FIELD SERVICE IN CHOENG NOEN DISTRICT, RAYONG PROVINCE - Amphonmaha, Pongsatron; Jarinto, Krit (RMUTT GLOBAL BUSINESS ACCOUNTING AND FINANCE REVIEW, 2018)
This research aimed at studying the consumer behavior deciding to choose the artificial turf football field service in the district of Choeng Noen in Rayong province in order to know what factors motivate the consumer to use the artificial turf football field service. The tools used in this research was the questionnaire survey and descriptive attribution card from 400 consumers who selected the artificial turf football field service to play football at Sri Mueang Park, Choeng Noen district, Rayong Province. Data analysis employed frequency and percentage. In addition, the financial analysis with Net Present Value (NPV), Internal Return of Investment (IRR) and payback period (PB) was applied in this study. The result indicated that most of respondents were single male students between 18-24 years old in Bachelor's degree and played football in Choeng Noen district. Those who answered “yes” in playing football, earned less than 10,000 bath. The consumers decided to use the artificial turf football field service in Choeng Noen district, Rayong province. The factors that motivated them to use the service include the size and type of the artificial football field, the promotion offering ‘10 hours, get 1 hour free’ and the price which was 600-900 baht per hour. Most of the respondents obtained the information from social media and chose to play football in the artificial turf football field 2-3 times a week. Lastly, the financial analysis including Payback period, NPV and IRR showed that an artificial turf football field is worth investing.